2003
DOI: 10.1046/j.1471-4159.2003.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency stimulation of the subthalamic nucleus enhances striatal dopamine release and metabolism in rats

Abstract: High-frequency stimulation of the subthalamic nucleus is believed to exert its main effects via the basal ganglia output structures. Previously, we have shown a concomitant increase in striatal dopamine (DA) metabolites in normal and 6-hydroxydopamine-lesioned rats. The present study was designed to determine whether this increase in striatal DA metabolites reflects enhanced intraneuronal DA turnover or, alternatively, is due to increased DA release with subsequent rapid and efficient reuptake and/or metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 48 publications
5
67
1
1
Order By: Relevance
“…The cortico-STN projection, which has been a focus of study for motor and premotor cortico-basal ganglia system, is termed the 'hyperdirect' basal ganglia pathway in that impulses reach the basal ganglia output nuclei faster via this route than through the cortico-striatal pathway (Kolomiets et al, 2003). Given that the STN impacts directly on DA cells (Rosales et al, 1994;Meissner et al, 2003), this route (PFC to the STN to the midbrain cells) may represent an alternative in the primate to the direct PFC-VTA/SN pathway observed in other species. In fact, PFC stimulation results in both excitatory and inhibitory responses in the primate SN pars reticulata, which are mediated via the STN and striatum, respectively (Kitano et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The cortico-STN projection, which has been a focus of study for motor and premotor cortico-basal ganglia system, is termed the 'hyperdirect' basal ganglia pathway in that impulses reach the basal ganglia output nuclei faster via this route than through the cortico-striatal pathway (Kolomiets et al, 2003). Given that the STN impacts directly on DA cells (Rosales et al, 1994;Meissner et al, 2003), this route (PFC to the STN to the midbrain cells) may represent an alternative in the primate to the direct PFC-VTA/SN pathway observed in other species. In fact, PFC stimulation results in both excitatory and inhibitory responses in the primate SN pars reticulata, which are mediated via the STN and striatum, respectively (Kitano et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, release was maximal at high frequencies ( ‡ 120 Hz) and voltages (7 V, highest tested). The use of a normal animal model weakens the therapeutic relevance of these findings, although microdialysis studies in rats with nigrostriatal lesions have also found increased striatal dopamine release by STN-DBS (Meissner et al, 2002(Meissner et al, , 2003.…”
Section: Substantia Nigra Pars Compactamentioning
confidence: 99%
“…Researchers have hypothesized that the level of DA and its metabolites in the corpus striatum are increased after STN-HFS. 1 Early reports showed that HFS increased major DA metabolic products in the striatum of 6-hydroxydopamine (6-OHDA) lesioned rats 15,16 . This result could explain the immediate improvement after the electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%